CIAT Fundraising Factsheets: Cocoa in Indonesia - International Center for Tropical Agriculture (2015)
These CIAT Fundraising Factsheets provide overviews of the following Cocoa in Indonesia issues: Upscaling Climate-Smart Agriculture; Data to understand adoption of improved cocoa production practices; Exposure maps: Cocoa suitability; Nationally Appropriate Mitigation Actions (NAMA) and Carbon Insetting; and Understanding carbon footprint and GHG emissions.